Evaluation of confirmatory data following the Article 12 MRL review for cymoxanil. (15th October 2019) - ,; Anastassiadou, Maria; Brancato, Alba; Carrasco Cabrera, Luis; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; Nave, Stefanie; Pedersen, Ragnor; et al.
Abstract: The applicant DuPont de Nemours (Deutschland) GmbH submitted a request to the competent national authority in Austria to evaluate confirmatory data identified for cymoxanil in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 and implemented in the EU MRL Regulation. To address the data gap on table and wine grapes, lettuce and spinach, the applicant submitted new residue trials for cymoxanil on these commodities. The data gap was considered satisfactorily addressed. Confirmatory data on analytical methods for enforcement in hops and herbal infusions (dried flower), and storage stability data in dry matrices were not submitted with the present application. Based on the available information, a revision of the existing MRLs for table and wine grapes, spinach and pulses should be considered by risk managers.